THE CONTRIBUTION OF THE EMPRESS MARIA FEODOROVNA INTO THE ORGANIZATION OF CHILDREN HEALTH CARE - G. L. Mikirtichan ("Paediatrician" Publishers LLC, 2013)
Sophie Marie Dorothea Auguste Louise descended from German House of Württemberg and was the eldest daughter of the prince Friedrich II Eugen, Duke of Württemberg. She turned into Orthodoxy under the name of Maria Feodorovna. In September 1776 she married the future emperor - Paul I. One of the most significant pages in the history of Russia is associated with the name of Maria Feodorovna - formation of the charity as a system, including three main directions: public education, social support and health care. With her direct assistance 30 charity institutions (founding hospitals, a number of women institutes and other teaching and educational organizations, alms-houses, hospitals etc.) were founded, most of them - for children.